Intellectual Property Rights for Plant Breeding and Rural Development : Challenges for Agricultural Policymakers - Tripp, Rob; Louwaars, Niels; Eaton, Derek (World Bank, Washington, DC, 2012)
Although many developing countries have drafted legislation to address plant variety protection (PVP) requirements, relatively few have begun to implement PVP, and little guidance is available on appropriate strategies. This note looks at some of the key decisions facing agricultural policymakers in establishing a PVP regime, examines the implementation of PVP, assesses some of the impacts and limitations of PVP regimes, and identifies policy priorities that complement the establishment of IPRs for plant breeding.